THE POTENTIAL OF AUGMENTED REALITY TO TRANSFORM EDUCATION INTO SMART EDUCATION - Nurul Fauziyyah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The paper used as a review material for this paper is "The Potential of Augmented Reality to Transform Education into Smart Education" by Gabriela Kiryakova, et al. published by TEM Journal Vol. 7 in 2018. In general, the paper reviewed the role of education in modern society that seeked to make life smarter in ordered to face the changing challenges of the world and strived to prepare students to become members of the community that were fully integrated with the living environment and technological developments. Smart education is an education system based on smart devices and smart technologies such as cloud computing, big data, and others. In an effort to implement smart education, augmented reality was implied. The specific purpose of the paper was to reveal the potential of augmented reality to transform traditional education into smart education. Augmented reality is considered as one of the technologies that can change learning significantly. In addition, the most important advantage of augmented reality compared to virtual reality is overcoming the risk of social isolation and lack of social skills and communication among users.